Okara-fortified wheat bread: effect on nutritional, physicochemical and sensory properties - Mustapha, Nor Afizah; Mahmud @ Ab Rashid, Nor Khaizura; Zainal Abedin, Nur Hanani; Wan Ibadullah, Wan Zunairah; Ibrahim, Nor Hayati; Mokhtar, Farhanah (Hibiscus Publisher Enterprise, 2024)
The increasing demand for low-calorie diets underlines the importance of creating food with a higher fiber content. This is particularly relevant regarding bread, as a significant proportion of the population consumes it. Okara is an underutilized insoluble residue rich in fiber and protein that is produced in large quantities in the soymilk processing industry. This study aims to investigate the effects of okara levels (0, 10, 15 and 20 %) on wheat bread's physicochemical, sensory, and storage properties. The fiber and protein content significantly increased, while the carbohydrate content decreased in okara-fortified bread. The browning index increased, while the specific volume of the bread decreased with increasing okara content. Nevertheless, the samples fortified with 10 % okara showed comparable textural properties to the okara-free samples. Okara delayed the retrogradation of bread, as demonstrated by a 5-day storage at room temperature. Bread fortified with a maximum of 15% okara was considered acceptable by the panelists, especially regarding taste and odor. This study suggests that okara could be potentially exploited as a new sustainable source of dietary fiber for bakery product applications.